Heart of barkness eaudiobook - Quinn, Spencer (Chet and Bernie Mystery, 2019)
Spencer Quinn's Heart of Barkness is the latest in the New York Times bestselling series that the Los Angeles Times called "nothing short of masterful". Chet the dog, "the most lovable narrator in all of crime fiction" (Boston Globe) and P.I. Bernie encounter heartache and much worse in the world of country music. They're both music lovers, so when Lotty Pilgrim, a country singer from long ago, turns up at a local bar, they drive out to catch her act. Bernie's surprised to see someone who was once so big performing in such a dive, and drops a C-note the Little Detective Agency can't afford to part with into the tip jar. The C-note is stolen right from under their noses - even from under Chet's, the nose that misses nothing - and before the night is over, it's stolen again. Soon they're working the most puzzling case of their career, a case that takes them back in time in search of old border-town secrets, and into present-day danger where powerful people want those secrets to stay hidden. Chet and Bernie find themselves sucked into a real-life murder ballad where there is no one to trust but each other.